Development of simulation tools to study the wear and degradation factors involved in rotating equipment in the process industry - Zapata Barros, Jefferson
This research project focuses on the study of the behavior of rotary axis machines under conditions of load, temperature, pressure, nature of movement and revolutions per minute, using a virtual simulator and a material one. With the purpose of obtaining information related to the root cause of the failures that are generated randomly, we seek to expand the range of events that will allow us to get closer to achieving a reduction in non-productive time due to equipment stoppage, we also seek to calculate and select the materials, lubricants, machine elements and acceptable conditions that guarantee the efficient operation of the entire line of production equipment.